TINJAUAN TERHADAP OBJEK TAMAN WISATA ALAM MAYANG KOTA PEKANBARU SEBAGAI PRODUK WISATA - Putri Maisandi; Firdaus Yusrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to describe the components of tourism products and to know the responses of tourists to Object of Taman Alam Mayang Tourism Park Pekanbaru City. This study uses quantitative descriptive method to process data obtained in the field through interviews, all the information collected and studied to become a unified whole (Kusuma and Sugono 2000). As for samples in the study as many as 100 people reponden, Data collection techniques used are observations, interviews, questionnaires, using Likert scale as a measuring tool. Based on the results of research that has been done tourism products on Object Nature Park Mayang has variables of Attraction / Tourism Attractions, Facilities, and Accessibility with a conclusion of good judgment.Keywords: Attraction, Facility, Accessibility, Object of Taman Wisata TourismPark